THE STUDY ON THE PRIMARY SEALING WITH COAXIAL ROUND-SHAPED SURFACES - Monica BÂLDEA; Mihaela ISTRATE; Alexandru BOROIU; Andrei-Alexandru BOROIU (Fiabilitate şi Durabilitate)
The paperwork studies the way of calculation of the interstitial pressure with Reynolds equation for the particular case of the primary sealing with coaxial round-shaped surfaces, one fixed and the other one rotating around Oz axis.